Preventive mental health at school : evidence-based services for students - Macklem, Gayle L. (Springer New York, 2014)
Some engage in high-risk behaviors. Others need help with emotional skills. Many are affected by mental disorders. While every school has its share of students needing comprehensive mental health services, personnel struggle to address these needs effectively in an era of scarce resources and dwindling budgets. Preventive Mental Health at School gives school-based practitioners and researchers an accessible, nuanced guide to implementing and improving real-world proactive programs and replacing outmoded service models. Based firmly in systems thinking and an ecological-public health approach, the book outlines the skills needed for choosing evidence-based interventions that are appropriate for all students, and for coordinating prevention efforts among staff, educators, and administration. As schools become more and more diverse, school-based practitioners must become knowledgeable in regard to the critical racial and cultural differences that affect students, their families, and enrich our schools. Research currently available to help meet the needs of various groups of children and their families is included as each topic is addressed. In addition, the author provides a theoretical groundwork and walks readers through the details of assessing resources and needs, applying knowledge to practice, and evaluating progress. Instructive case examples show these processes in action, and further chapters address questions of adapting programs already in place for greater developmental or cultural appropriateness. Included in the coverage: Student engagement, motivation, and active learning. Engaging families through school and family partnerships. Evidence-based prevention of internalizing disorders. Social emotional learning. Adapting programs for various racial and ethnic populations. Adapting programs for young children. Preventive Mental Health at School offers solid guidance and transformative tools to researchers, graduate students, and professionals/practitioners/clinicians in varied fields including clinical child and school psychology, social work, public health and policy, educational policy and politics, and pediatrics.